2018
DOI: 10.1002/dev.21783
|View full text |Cite
|
Sign up to set email alerts
|

Development of the other‐race effect in Malaysian‐Chinese infants

Abstract: Little is known about how infants born and raised in a multiracial environment process ownand other-race faces. We investigated face recognition of 3-to 4-month-old (N = 36) and 8to 9-month-old (N = 38) Chinese infants from Kuala Lumpur, Malaysia, a population that is considered multiracial, using female and male faces that are of infants' own-race (Chinese), experienced other-race (Malay) and less experienced other-race (Caucasian-White). Three-to 4-month-olds recognised own-race female faces, whereas 8-to 9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
8
20
0
Order By: Relevance
“…Singh et al, 2017;Tree et al, 2017). Given the existing evidence that Malaysians interact with other races less when they are children (Kawangit et al, 2012;Su et al, 2018), the robustness of ORB in the multiracial population implies a relative lack of perceptual experience with other-race faces during childhood (de Heering et al, 2010;Su et al, 2018;Mckone et al, 2019; see also Sangrigoli et al, 2005). Additionally, the magnitude of ORB was modulated by the presence/absence of external features, such that other-race faces without external features were recognized poorly.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Singh et al, 2017;Tree et al, 2017). Given the existing evidence that Malaysians interact with other races less when they are children (Kawangit et al, 2012;Su et al, 2018), the robustness of ORB in the multiracial population implies a relative lack of perceptual experience with other-race faces during childhood (de Heering et al, 2010;Su et al, 2018;Mckone et al, 2019; see also Sangrigoli et al, 2005). Additionally, the magnitude of ORB was modulated by the presence/absence of external features, such that other-race faces without external features were recognized poorly.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, there is evidence that Malaysians interact with other races less when they are children than when they are adults. The low level of interracial contact during infant and childhood in Malaysians is commonly reflected through same-race primary caregivers (Su et al, 2018) and the racially segregated educational systems in primary and secondary schools (Kawangit et al, 2012). For instance, Kawangit et al (2012) reported that the Chinese usually sent their children to Chinese schools with their syllabi adopted from Mainland China; Malays sent their children to Madrasa (religious schools), and Indians to Tamil schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, infant face processing researchers have generated substantial data demonstrating how infants' social experience is related to their face recognition abilities. For example, infants ranging in age from 3 to 16 months show more difficulty discriminating among exemplars of men's faces than women's faces [1][2][3][4]. Similarly, race familiarity affects infant face processing.…”
Section: Introductionmentioning
confidence: 99%
“…Infants’ attention during familiarization might also be related to the facial expression posed by the model. Most studies examining infants’ recognition of familiar and unfamiliar face types have utilized images with neutral expressions [ 2 , 3 , 4 , 6 , 7 , 8 ], but most infants do not typically experience neutral faces and tend to respond negatively to such faces as in the still-face paradigm [ 27 ]. Four- to 6-month-olds look longer at smiling than neutral faces and typically learn to categorize happy emotions first, likely due to most infants’ familiarity with positive expressions [ 28 , 29 ], so infants might scan and process pleasant and neutral expression faces differently.…”
Section: Introductionmentioning
confidence: 99%